Phase portraits of Abel quadratic differential systems of the second kind. Issue 4 (2nd October 2018) - Ferragut, Antoni; Valls, Claudia
ABSTRACT: We provide normal forms and the global phase portraits on the Poincaré disk of some Abel quadratic differential equations of the second kind. Moreover, we also provide the bifurcation diagrams for these global phase portraits.